2011
DOI: 10.2182/cjot.2011.01.78.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Enabling University Teaching for Canadian Academics with Multiple Sclerosis through Problem-Focused Coping

Abstract: This brief report is intended to serve as a resource for occupational therapists and others wanting to gain a better understanding of the types of therapeutic interventions useful to those teaching in universities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…A number of studies listed various types of work accommodations (e.g., technological devices, working from home), which could help a worker with a chronic condition perform the job tasks while managing (or alleviating) symptoms and maintaining productivity (Bogenschutz et al, 2016;Bose, 2013;Burda et al, 2012;Codd et al, 2010;Holland & Collins, 2016;Lacaille et al, 2007;Osterholm et al, 2013;Restall et al, 2016;Sweetland et al, 2007;Zhao et al, 2017). Numerous studies showed that having job control opportunities such as working from home, starting later or alternating tasks all helped to manage fluctuations in symptoms, since work could be fitted to daily symptoms and more time was available for self-care (Bogenschutz et al, 2016;Crooks, Stone, & Owen, 2011;Dickson et al, 2008;Holland & Collins, 2016;Lacaille et al, 2007;Osterholm et al, 2013;Restall et al, 2016;Van der Meer et al, 2011).…”
Section: Requesting Work Accommodations and Supportmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies listed various types of work accommodations (e.g., technological devices, working from home), which could help a worker with a chronic condition perform the job tasks while managing (or alleviating) symptoms and maintaining productivity (Bogenschutz et al, 2016;Bose, 2013;Burda et al, 2012;Codd et al, 2010;Holland & Collins, 2016;Lacaille et al, 2007;Osterholm et al, 2013;Restall et al, 2016;Sweetland et al, 2007;Zhao et al, 2017). Numerous studies showed that having job control opportunities such as working from home, starting later or alternating tasks all helped to manage fluctuations in symptoms, since work could be fitted to daily symptoms and more time was available for self-care (Bogenschutz et al, 2016;Crooks, Stone, & Owen, 2011;Dickson et al, 2008;Holland & Collins, 2016;Lacaille et al, 2007;Osterholm et al, 2013;Restall et al, 2016;Van der Meer et al, 2011).…”
Section: Requesting Work Accommodations and Supportmentioning
confidence: 99%
“…However, studies pointed out that asking for support appeared to be difficult for some workers. Several studies showed important conditions for requesting support, which included accepting the need for support and pointing out specific needs (Bose, 2013;Burda et al, 2012;Crooks et al, 2011;Lacaille et al, 2007;Stanley et al, 2007). Condition unpredictability and symptom fluctuations made it even more difficult to ask for support.…”
Section: Requesting Work Accommodations and Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the studies dealing with the association between coping and HRQoL in MS patients have a significantly lower number of participants [10][11][12] or focused on women only [13]. Some of them use variables that are only partly responsible for overall HRQoL such as fatigue [14], coping in dyadic relationships [15] or focusing only on positive effect of problem-focused coping [16]. However, there is no study addressing all these three types of coping at once so this study tries to put another piece of the puzzle into the overall picture of this field of research.…”
Section: Introductionmentioning
confidence: 99%